Lyapunov Based Observer Design for Electro-Hydraulic Arm System - Serkan Aksoy; Mithat Önder; Alper Bayrak (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2022)
In this paper, a Lyapunov based observer design is proposed to observe the load pressure of electro-hydraulic arm systems. The stability of the observer is investigated by using the Lyapunov based method. In the stability analysis, it is proven that the observer error converge to the vicinity of origin which can be adjusted to be arbitrarily small. The classical PID controller is used to control the position of the electro-hydraulic arm system and keep the system states bounded. The performance of the designed observer is evaluated by computational simulations which are conducted in MATLAB Simulink program. The performance of the observer is tested in two cases: i) noise free case and ii) noise case. In the noisy case, the state x_2 is exposed to the 30 dB additive white Gaussian noise. The computational simulation results are given to demonstrate that the proposed observer work efficiently in both noise free and noisy cases.